2009
DOI: 10.1007/978-3-642-04747-3_20
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Community Detection Algorithms on Artificial Networks

Abstract: Abstract. Community detection has become a very important part in complex networks analysis. Authors traditionally test their algorithms on a few real or artificial networks. Testing on real networks is necessary, but also limited: the considered real networks are usually small, the actual underlying communities are generally not defined objectively, and it is not possible to control their properties. Generating artificial networks makes it possible to overcome these limitations. Until recently though, most wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 40 publications
(86 reference statements)
5
86
0
Order By: Relevance
“…In this section, we first describe the LFR model we applied during the first step, which supposedly allows generating the most realistic networks in terms of overall properties (degree distribution, smallworldness, etc.) [6,10,11]. Then, we shortly describe the community detection algorithms we selected, and explain how they differ on the way they handle the concept of community.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we first describe the LFR model we applied during the first step, which supposedly allows generating the most realistic networks in terms of overall properties (degree distribution, smallworldness, etc.) [6,10,11]. Then, we shortly describe the community detection algorithms we selected, and explain how they differ on the way they handle the concept of community.…”
Section: Methodsmentioning
confidence: 99%
“…It increased the realism level even more by generating networks with power-law distributed degree. Among these newer models, we selected the LFR model, which seems to be the more realistic and was previously used as a benchmark to compare community detection algorithms [6,10,19]. The LFR model was proposed by Lancichinetti et al [6] to randomly generate undirected and unweighted networks with mutually exclusive communities.…”
Section: Network Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different community detection algorithms presented in the paper [1]. In this paper, we use a heuristic algorithm called a Louvian method [2] based on modularity optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Optimisation algorithms include several approaches: greedy routing (Newman, 2004), simulated annealing (Guimera et al, 2004), spectral optimisation (Newman, 2006a), game-theoretic (Narayanam and Narahari, 2010;Chen et al, 2010), compression-based (Rosvall and Bergstrom, 2007) and flow-based (Wu and Huberman, 2004). Reviews of the various methods present in the literature can be found in Danon et al (2005) and Orman and Labatut (2009).…”
Section: Introductionmentioning
confidence: 99%